-18p-6(5-4p)=4(p-3)-12

Simple and best practice solution for -18p-6(5-4p)=4(p-3)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18p-6(5-4p)=4(p-3)-12 equation:


Simplifying
-18p + -6(5 + -4p) = 4(p + -3) + -12
-18p + (5 * -6 + -4p * -6) = 4(p + -3) + -12
-18p + (-30 + 24p) = 4(p + -3) + -12

Reorder the terms:
-30 + -18p + 24p = 4(p + -3) + -12

Combine like terms: -18p + 24p = 6p
-30 + 6p = 4(p + -3) + -12

Reorder the terms:
-30 + 6p = 4(-3 + p) + -12
-30 + 6p = (-3 * 4 + p * 4) + -12
-30 + 6p = (-12 + 4p) + -12

Reorder the terms:
-30 + 6p = -12 + -12 + 4p

Combine like terms: -12 + -12 = -24
-30 + 6p = -24 + 4p

Solving
-30 + 6p = -24 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
-30 + 6p + -4p = -24 + 4p + -4p

Combine like terms: 6p + -4p = 2p
-30 + 2p = -24 + 4p + -4p

Combine like terms: 4p + -4p = 0
-30 + 2p = -24 + 0
-30 + 2p = -24

Add '30' to each side of the equation.
-30 + 30 + 2p = -24 + 30

Combine like terms: -30 + 30 = 0
0 + 2p = -24 + 30
2p = -24 + 30

Combine like terms: -24 + 30 = 6
2p = 6

Divide each side by '2'.
p = 3

Simplifying
p = 3

See similar equations:

| 7x^2+151x-1372=0 | | 11y-8=5y+16 | | 8w-3=5w+18 | | ln(x+2)=7-ln(x+2) | | -81=6v-13v-18 | | -5x-19=0 | | x^3-7x+6=x^2+2x-3 | | 7x^2+6=-118 | | 2x+y=31xy | | 7x^2-24x-9=0 | | 6x+2y+6x= | | 4x(-6)=4x(-5) | | -4(-6v-u)-3(3u+5v)= | | g(-4)=-4x-4 | | -2a^2+22a+121=0 | | a^2+22a+121=0 | | 8x+5=10x+23-8x | | (-3)(12)= | | x-29=19 | | 18=6(w+6)-8w | | 8x+2=1x-19 | | 5v-41=-6(v-6) | | 2m+12=-31 | | -2+2x=4+12x | | Y=-4x+340 | | 2x^2-5x-21=p | | 3b-3(-23+2b)=48 | | 5(x-3)-x= | | Tanx-cotx=0 | | 22=-3+5u | | 2(7p+8)+6(2p+8)= | | 10-5x-10x+4= |

Equations solver categories